Pemanfaatan Media Sosial Twitter oleh Ridwan Kamil dan Ganjar Pranowo Telah Sesuai dengan Fungsi Utama Media Massa - Harrera, Andrea Eka Premasadha (Universitas Semarang, 2016)
The development of social media makes a lot of people should follow it. We are required to be able to use social media as a medium that can simplify our lives, as we can find a lot of information or news through the media. On the other hand, social media can also facilitate the work of someone. In this research, the researcher want to see that social media twitter belonging to Ridwan Kamil and Ganjar Pranowo which they use as a medium to get closer to the citizens, in accordance with the essential function of the mass media. This research using qualitative research method with observation the timeline twitter of @ridwankamil and @ganjarpranowo. Then, from the observation, It is indicate that the twitter account has complied with all the essential functions of a mass media.